Global prevalence of Candida species diversity in oral cavity of denture wearing patients- A systematic review and meta analysis (Bangladesh Journal of Medical Science, 2025)
Aim in order to give current evidence regarding the diversity of candida species in individuals who have dentures or who suffer from denture stomatitis (DS). Methods The study was registered in PROSPERO and followed the PRISMA guidelines for systematic reviews and metaanalyses. Patients with dentures or denture stomatitis were the subjects of a comprehensive literature search that spanned the years 2000–2023. The goal was to find studies that measured the prevalence of multiple species of candida that colonise denture patients. In order to determine the studies’ quality, the Newcastle Ottawa scale (NOS) was used. Employing a random-effect model with a significance level set at p